A study on climate change impacts using lumped versus distributed hydrological models in a semi-arid basin - Farahnaz Baharvand; Ali Reza Massah Bavani; Mohammad Mahdavi; Massoud Goodarzi (Anthropogenic Pollution)
This paper, aims to evaluate the impacts of potential climate change on the stream flow of a semi-arid catchment (called Merek) in western Iran using Distributed Catchment Scale Model (DiCaSM) and IHACRES lumped model and compare their ability in simulation of the future stream flow in this area. The joint probability plot was used to generate seasonal climatic change factors (% change in rainfall and change in temperature °C) to apply as an input to the DiCaSM model. A suite of 15 Atmosphere-Ocean Global Circulation Models (AOGCMs) from the Coupled Model Inter-comparison Project (CMIP) with monthly rainfall and temperature data for the baseline period were evaluated. By analyzing the models, finally, the three best models, including GFDL-CM3, CNRM-CM5 and NorESM1-M models, which reproduce the climatic behavior of monthly temperature and precipitation values, were selected. To study the impact of future climatic change on water supply, this study applied the RCP Scenarios. It proved an acceptable performance in reproducing of the historical observations three Representative Concentration Pathways (RCP 2.6, RCP4.5, and RCP8.5) scenarios for the future period 2040-2069. Results indicated that both hydrological models were able to simulate the observed stream flow successfully in the study catchment. The projections of three AOGCMs showed that the future temperature would be increased in the area, while there was no agreement between the models in simulation of future rainfall. Changes in stream flow simulated by DiCaSM model were ranged from -5.2% to 6.2% for the period 2040-2069, while for IHACRES model, the changes ranged from -37.7% to 10.1%. Overally the model performed extremely well for both the calibration and validation years. It is recommended to use these hydrological models for a general evaluation of climate change impact in water resources studies.